40Ar/39Ar DATING OF THE STAGE OF TRANSFORM-SHEAR DEFORMATION IN EVOLUTION OF THE EARLY CALEDONIDES IN WESTERN SANGILEN, SOUTHEASTERN TUVA - Barabash N.V.; Vladimirov V.G.; Travin A.V.; Yudin D.S. (My University, 2007)
In paleotectonic reconstructions of the Central Asian Foldbelt (CAFB), special attention is paid to the Early Paleozoic processes of the formation and breakdown of orogenic edifices. In this regard, the results of geological and isotopic studies of the southern framework of the Siberian Craton attract interest, because they provide chronological links between accretion and collision, on the one hand, and reactivation of magmatic processes, on the other. In line with these investigations, we investigated the scale and duration of the evolution of the CAFB that underwent all evolution stages ranging from Late Vendian subduction and accretion to Cambrian collision and the Ordovician stage of transform-shear deformation in the Sangilen region, an Early Caledonian fragment of CAFB in southeastern Tuva. The PTdt model proposed in this work illustrates periods of origination and reactivation of the main tectonic deformation of the region: the Agardag suture zone and the Erzin and Kokmolgarga shear zones. These and related deformations of the lower rank compose the West Sangilen strike-slip system, the evolution of which led to fragmentation of crust into large tectonic blocks (Tannuol, Mugur–Chinchilig, and Erzin–Naryn).
Keywords: Paleozoic::Ordovician; Палеозой::Ордовикская